2010
DOI: 10.1016/j.mrgentox.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenicity of oxidized DNA precursors in living cells: Roles of nucleotide pool sanitization and DNA repair enzymes, and translesion synthesis DNA polymerases

Abstract: The base moieties of DNA precursors in the nucleotide pool are subjected to oxidative damage, and the formation of damaged DNA precursors is an important source of mutagenesis. 8-Hydroxy-2'-deoxyguanosine 5'-triphosphate, also known by the name of its keto-enol tautomer as 8-oxo-7,8-dihydro-2'-deoxyguanosine 5'-triphosphate, and 2-hydroxy-2'-deoxyadenosine 5'-triphosphate have been identified as the major products of in vitro oxidation reactions. The mutagenicities of these damaged precursors in living cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…Nucleotide pool sanitization, the specific hydrolysis of damaged DNA precursors, is an important means by which organisms prevent mutations [48, 49]. In mammalian cells, the MTH1 (NUDT1), MTH2 (NUDT15), and NUDT5 proteins catalyze the hydrolysis of dG O TP and/or its diphosphate derivative to produce the monophosphate compound [5053].…”
Section: Introductionmentioning
confidence: 99%
“…Nucleotide pool sanitization, the specific hydrolysis of damaged DNA precursors, is an important means by which organisms prevent mutations [48, 49]. In mammalian cells, the MTH1 (NUDT1), MTH2 (NUDT15), and NUDT5 proteins catalyze the hydrolysis of dG O TP and/or its diphosphate derivative to produce the monophosphate compound [5053].…”
Section: Introductionmentioning
confidence: 99%
“…Relevant information has also been gained on the removal of oxidatively damaged DNA that for single modified bases and abasic sites is predominantly mediated by base excision repair [2124]. In addition, the mutagenic features of most oxidized bases and several clustered DNA lesions have been determined [21,2426]. Insights into the ability for translesional synthesis polymerases to bypass blocking DNA lesions have also been gleaned [26].…”
Section: Introductionmentioning
confidence: 99%
“…This result suggested that DNA pol l is involved in the mutagenesis processes of G O , generated by dGTP oxidation in the nucleotide pool. In addition to the DNA pols, other cellular enzymes play crucial roles in the mutagenesis processes of damaged DNA and DNA precursors (40). Experiments to reveal their roles are currently in progress.…”
Section: Resultsmentioning
confidence: 99%